Temperature effects in the magnetic properties of two-dimensional Ising square lattices: A Monte Carlo investigation - Yongyut Laosiritaworn (2018)
The magnetic behavior of a two-dimensional nearest-neighbor Ising model with the presence of linear temperature variation in a thermal steady state was studied using the Wolff Monte Carlo simulation. The technique consists of fixing the temperatures of boundary spins, while the temperature field in the interior linearly varies with distance. It is found that with increasing the temperature difference between the two boundaries, the magnetization greatly reduces in magnitude while the susceptibility peaks tend to spread out over a temperature range. The detailed descriptions of these magnetization and susceptibility behaviors are elucidated from their spatial variation. The extraction of the "critical temperatures" is taken via the fourth-order cumulant of the magnetization. The critical temperatures are found to reduce slightly with increasing the temperature difference. This implies the vulnerability of the magnetization and susceptibility properties to the temperature variation in ferromagnetic materials, and to use such materials in temperature variation environments must be done with caution. © 2007 The American Physical Society.